ANALISIS YURIDIS TERHADAP WARISAN YANG BELUM TERBAGI SEBAGAI SUBJEK PAJAK BERDASARKAN UNDANG-UNDANG PAJAK PENGHASILAN - DIANA PUTRI TRISNA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. Suprayitno, SH, MKn2. Dr. Dedi Harianto, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHum According to Article2, paragraph 1, letter b of UU PPh (Law on IncomeTax), undistributed inheritance as a unit which substitutes heirs is called asubstitute Tax Subject. It is intended to impose PPh which comes from inheritanceby using testator’s NPWP (Taxpayer’s ID Number) deposited by the heir. Theresearch problems are how about why undistributed inheritanceis used as thesubject of PPh, how about the fulfillment of the principle of legal certainty indetermining undistributed inheritance as the subject of PPh, and how about theprinciple of justice in regulating undistributed inheritance for substituting testatoras the subject of PPh. The research used juridical normative and descriptiveanalytic method.Keywords: Income Tax, Undistributed Inheritance